Interventions for Addressing Anemia Among Children and Adolescents: An Overview of Systematic Reviews - Prasanna Mithra; Mahalaqua Nazli Khatib; Anju Pradhan Sinha; Nithin Kumar; Ramesh Holla; Bhaskaran Unnikrishnan; Ratheebhai Vijayamma; N. Sreekumaran Nair; Abhay Gaidhane; Syed Quazi Zahiruddin (Frontiers Media S.A., 2021)
Context: Anemia is a public health problem that can lead to growth, cognitive, and motor impairments.Objective: To collate evidence on interventions for addressing childhood and adolescent anemia.Methods: In this overview of systematic reviews, we included Cochrane as well as non-Cochrane systematic reviews (SRs) irrespective of language and publication status. Two sets of review authors independently screened articles for eligibility and extracted data from relevant SRs. We present data in a tabular format and summarize results based on outcome reported, age of participants, and type of interventions. We also adopt a "measurement for change" approach to assess the utility of measurement for development of interventions in childhood and adolescent anemia.Results: Our search yielded 2,601 records of which 31 SRs were found eligible for inclusion. Results were favorable for fortification and supplementation with clear reduction in the risk of anemia and increase in hemoglobin levels across all age groups. Other interventions reported by the SRs were inconclusive and suggest further research.Conclusions: Current evidence suggests that fortification or supplementation with iron and micronutrients leads to better reduction in the risk of anemia and improvements in hemoglobin levels among children and adolescents. Results of this overview can help decision makers in informing selection of interventions to address childhood and adolescent anemia.Review Registration: PROSPERO CRD42016053687.